Constructing atomic Co1–N4 sites in 2D polymeric carbon nitride for boosting photocatalytic hydrogen harvesting under visible light. (22nd March 2022) - Liu, Xuecheng; Mateen, Muhammad; Cheng, Xianke; Wu, Dongqing; Zhang, Jie; Cheong, Weng‒Chon; Liu, Shoujie
Abstract: Two‒dimensional polymeric carbon nitride (2DPCN) is a versatile support for constructing single atom catalysts (SACs). Herein, we demonstrated a facile strategy for constructing atomic Co sites on 2DPCN. Atomic dispersion of Co was confirmed by the aberration‒corrected high angle annular dark field scanning transmission electron microscopy, while the extended X‒ray absorption fine structure spectroscopy analysis precisely corroborated the existence of atomic Co 1 –N4 non square planar sites on 2DPCN support. Remarkably, Co 1 /2DPCN catalyst yielded H2 at a rate of 28.3mmolH2 h −1 gCo −1, which is approximately 4.2 times higher than that of CoNPs/2DPCN (6.8mmolH2 h −1 g Co −1 ) counterpart. Notably, with 0.75 wt % Pt as a co‒catalyst, H2 evolution activity for Co 1 /2DPCN and CoNPs/2DPCN reached as high as 138.6 mmolH2 h −1 gmetal −1 and 22.4mmolH2 h −1 gmetal −1, respectively, which could be attributed to the synergistic effect of atomic Co 1 –N4 sites and Pt. Both DFT calculations and spectroscopic results revealed that as constructed atomic Co 1 –N4 sites, reduced band gap energy, improved light harvesting ability and decreased energy barrier for H2 evolution. Graphical abstract: Image 1 Highlights: Demonstrated facile synthesis of Co single atoms on 2D polymeric carbon nitride support (Co 1 /2DPCN). XAS analysis revealed the presence of distinct non square planar Co–N4 atomic sites. Atomic Co–N4 sites promoted light absorption and directional charge transfer. The atomic Co 1 /2DPCN catalyst achieved 28.3mmolH2 h −1 gCo −1 activity without the assistant of noble metal co‒catalyst. Proposed H2 evolution mechanism on the basis of experimental results and DFT calculations.